Validated LC-MS/MS Method for Simultaneous Quantitation of Enasidenib and its Active Metabolite, AGI-16903 in Small Volume Mice Plasma: Application to a Pharmacokinetic Study - Dittakavi, Sreekanth; Hallur, Gurulingappa; Purra, Buchi Reddy; Kiran, Vinay; Zakkula, Ashok; Mullangi, Ramesh (Drug Research, 2020)
Enasidenib is a selective mutant isocitrate dehydrogenase 2 inhibitor approved for the treatment of relapsed and refractory acute myeloid leukemia patients. A sensitive and rapid method has been developed and validated as per regulatory guideline for the simultaneous quantitation of enasidenib and its active metabolite, AGI-16903 in mice plasma using an LC-MS/MS. Enasidenib and AGI-16903 along with internal standard were extracted from mice plasma using simple protein precipitation method. Chromatographic resolution of enasidenib, AGI-16903 and the internal standard (close analogue of AGI-16903) was achieved on a Chromolith RP-18e column using 0.2% formic acid:acetonitrile (15:85, v/v) as an eluent, which was delivered at a flow-rate of 1.2 mL/min. The MS/MS ion transitions monitored were m/z 474.1→267.2, 402.1→188.1 and 421.0→146.1 for enasidenib, AGI-16903 and the internal standard, respectively. The linearity range was 1.01–3023 ng/mL for both enasidenib and AGI-16903. The within-run and between-run accuracy and within-run and between-run precision were in the range of − 2.29 to 2.72 (as one value is in negative side). and 4.65–9.82%, respectively for enasidenib; 0.19–10.3 and 3.22–9.22%, respectively for AGI-16903. Both enasidenib and AGI-16903 were found to be stable in stability (up to three freeze-thaw cycles and for long-term at −80°C for 30 days) and processed (bench-top for 6 h and in in-injector for 24 h) samples. Application of the validated method was shown in a pharmacokinetic study in mice.
Keywords: enasidenib; AGI-16903; mice plasma; LC-MS/MS; method validation; pharmacokinetics